Lumbar punctures based on computerized tomography scans combined with precise calculations: a new lumbar puncture technique for spinal muscular atrophy patients with scoliosis - Hongyuan Li; Juan Du; Xi Chen; Hanbing Lu; Yan Jiao; Shuyu Dong (Frontiers in Neurology)
ObjectiveWe report our experience performing lumbar punctures using a novel technique in (Spinal muscular atrophy) SMA patients with scoliosis.MethodsA retrospective case series was conducted at the Department of Neurology at Xuzhou Central Hospital from January 2022 to August 2024. Patients diagnosed as SMA combined with scoliosis underwent 58 lumbar punctures using a novel guidance technique. Data on first pass success rate, needling time, using of sedation and adverse events (AEs) were collected and analyzed.ResultsA total of 58 successful lumbar punctures were performed on six SMA patients with scoliosis using this novel technique. Most patients achieved first pass success for each LP, except for one patient. The media first LP needling time was 70.5 s (range: 45 s−150 s). For subsequent procedures, the needling time was shorter than for the first LP in all patients. Apart from one instance of back pain and one case of post-puncture headache, no other AEs were observed.ConclusionLumbar punctures guided by a single CT scan combined with precise calculations can be broadly and safely applied for intrathecal injection in patients with scoliosis.